Design and evaluation of a low flow personal cascade impactor. Issue 2 (1st February 2018) - Chen, Modi; Romay, Francisco J.; Marple, Virgil A.
ABSTRACT: A very compact cascade impactor with 2 L/min sampling flow rate has been developed. Its dimensions are 8.5 cm L x 5.0 cm W x 11.4 cm H, and it weighs 0.27 kg, with ten impaction stages with aerodynamic cutpoints in the range of 60 nm to 9.6 μm. The top eight stages, collecting particles down to 170 nm in aerodynamic diameter, can be used as a stand-alone impactor with a portable, battery-powered pump. Particle collection efficiencies were obtained with two types of commonly used substrates, aluminum foil and glass fiber filters. Impactor cutpoints with aluminum foil substrates agree well with conventional impactor theory. The efficiency curves are sharp with minimum overlap between them. Thus, the compact impactor design does not compromise its performance, making it suitable for general purpose applications where a lower sampling flow rate provides adequate mass collection. With glass fiber filter substrates, impactor cutpoints are smaller and the efficiency curves are less steep, in particular for the last stages. Also, the collection efficiency curves do not drop to near zero at small Stokes numbers. Instead, excess particle collection efficiency of around 10% is observed for the top six stages, and becomes higher for the last four stages. This is due to the collection of particles by filtration as the impinging jets penetrate the filter substrate. Thus, using glass fiber filter substrates should generally be avoided due to the non-ideal effect on the impactor collection efficiency curves, especially for the last two stages. Copyright © 2018 American Association for Aerosol Research